Determinants of infant mortality in last two decades: a bibliometric analysis - Taskaya, Serap; Demirkiran, Mustafa (International Journal Of Community Medicine And Public Health, 2017)
Background: Infant mortality has a great importance as a measurement of child survival year by years. The first aim of this study was to determine the predictors of infant mortality in last two decades with a bibliometric and a content analysis. A secondary objective was to examine the frequency of publications by year, the distribution of articles by country location and, to determine how data were collected and analyzed. Methods:It was a bibliometric analysis of web of science database for years 1996-2015. A total of 289 eligible articles were identified. The publications were analyzed by publication years, contributions of the countries, data collection tools, study designs and determinants. Results: The annual number of infant mortality related articles increased from 7 articles in 1996 to 27 articles in 2015. The largest studies were made in the USA. Many of articles used records, national statistics or cohort study for data collection. Logistic and linear analysis model were performed commonly. Illness/infection, birth weight, and gestational age were the most important factors affecting infant mortality. Conclusions:This study provides a useful reference to researchers for the future research directions. The results of this study are also expected to provide evidence-based information to health policymakers to evaluate the best policy approaches for efforts on reducing infant mortality.